Development of Procedures for Medium- and Long-term Storage of Coast Redwood (Sequoia sempervirens) - Kirdok, Emrah; Ozden-Tokatli, Yelda; Capuana, Maurizio; Ozudogru, Elif Aylin (Springer, 2009)
[No abstract available]